The Relationship between Neutrophil-Lymphocyte Ratio to Intestinal Viability in Invagination Patients at Dr. M. Djamil General Hospital, Padang, Indonesia - Ranuta, Romi; Jon Efendi; Budi Pratama Arnofya; Yevri Zulfiqar; Benni Raymond; Hendra Maska (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Invagination is an acute condition in the pediatric abdomen that results in obstruction and constriction of blood vessels (strangulation) in the proximal intestinal mesenterium trapped in the distal intestine, allowing necrosis of surrounding tissue. Intestinal necrosis and perforation in children are causes of abdominal emergencies that require immediate surgery. In supporting examinations, neutrophil, lymphocyte, and biomarker combination ratios have been used for early detection of systemic inflammatory markers. The threshold value of several biomarkers should be investigated to assess the occurrence of strangulation in the pre-operative period in invaginated patients. This study aimed to determine the relationship between neutrophil-lymphocyte ratio and intestinal viability in pediatric patients with invagination. Methods: This study used retrospective analytic data collection from medical records of invagination patients at Dr. M. Djamil General Hospital Padang for the period January 1, 2020, to December 31, 2022. Results: The majority of subjects were male (53.8%) at the age of ≤ 1 year, with as many as 87.2% having a diagnosis of operative invagination (76.9%) and 56.4% having intestinal viability. The mean neutrophil, lymphocyte, and NLR values were 62.15±17.68, 19.03±8.97, and 3.74±1.55, respectively. The pathological NLR status was found to be 59%. The p-value for the association of diagnosis with intestinal viability was 0.002. The p-value for the relationship between NLR and intestinal viability was 0.001, and the r-calculated was -0.528. Conclusion: There is a significant relationship between NLR value and disease diagnosis on intestinal viability.